2014
DOI: 10.1038/bmt.2014.215
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-transplant co-morbidities on outcome after alemtuzumab-based reduced intensity conditioning allo-SCT in elderly patients: A British Society of Blood and Marrow Transplantation study

Abstract: The advent of reduced intensity conditioning (RIC) regimens has permitted the extension of allo-SCT to selected patients into their eighth decade but GVHD remains a major cause of morbidity and mortality. Alemtuzumab is increasingly used to reduce the risk of severe GVHD, but there are concerns that T-cell depletion may compromise outcome particularly in older patients. We therefore studied the impact of pre-transplant factors on the outcome of 187 patients with a haematological malignancy over the age of 60 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The widely used, updated HCT-CI score allows some adjustments due to age ( 73 ), and this analysis showed that younger patients with comorbidities were at a significant disadvantage to older fit individuals with no other significant comorbidities. Nonetheless the HCT-CI score is still of importance in this population, as it has been shown that in patients above 60 years of age a HCT-CI score of 2 or greater results in substantially higher TRM than otherwise expected ( 78 ). Future developments to improve assessment of transplant eligibility in this cohort should involve geriatric assessments that encompass an assessment of the functional status of the patient ( 79 ).…”
Section: Introductionmentioning
confidence: 99%
“…The widely used, updated HCT-CI score allows some adjustments due to age ( 73 ), and this analysis showed that younger patients with comorbidities were at a significant disadvantage to older fit individuals with no other significant comorbidities. Nonetheless the HCT-CI score is still of importance in this population, as it has been shown that in patients above 60 years of age a HCT-CI score of 2 or greater results in substantially higher TRM than otherwise expected ( 78 ). Future developments to improve assessment of transplant eligibility in this cohort should involve geriatric assessments that encompass an assessment of the functional status of the patient ( 79 ).…”
Section: Introductionmentioning
confidence: 99%
“…22 It is of particular value in patients older than 60 years in whom transplant decision making can be very complex. 26 Importantly, while the TRM of patients older than 60 years with an HCT-CI of 0 to 1 is broadly similar to that observed in younger patients, it is clear that older patients tolerate comorbidities less well than do younger patients, and the TRM in patients older than 60 years whose HCT-CI is greater than 3 can be as high as 60%. Despite this, predicting the impact of patient fitness on transplant outcome still remains imprecise, particularly in older patients, and the decision to recommend allo-SCT remains bespoke.…”
Section: Eligibility For Allo-sct and The Impact Of Novel Therapiesmentioning
confidence: 60%
“…An alternative TRM assessment tool is the EBMT scoring system which was first devised to assess outcome of allogenic stem cell transplant for patients with chronic myeloid leukemia ( 55 ), but is now not widely used in assessing patients with AML ( 56 ). Whilst the EBMT scoring and HCT-CI take different parameters into account neither perform particularly well in older patients destined for RIC allografts where studies have shown an excess TRM in patients with an HCT-CI>1 ( 57 ). Attempts to combine the two methods to develop a compounded scoring system has been shown to improve TRM prediction ( 55 , 56 ).…”
Section: Which Patients With Aml Should Be Transplanted In First Remission?mentioning
confidence: 99%